Increased surfactant protein‐D levels in the airways of preterm neonates with sepsis indicated responses to infectious challenges. (8th January 2019) - Mackay, Rose‐Marie A.; Townsend, J. Paul; Calvert, Jennifer; Anthony, Mark; Wilkinson, Andrew R.; Postle, Anthony D.; Clark, Howard W.; Todd, David A.
Abstract: Aim: Sepsis is multifactorial and potentially devastating for preterm neonates. Changes in surfactant protein‐D (SP‐D), phosphatidylcholine (PC) and PC molecular species during infection may indicate innate immunity or inflammation during sepsis. We aimed to compare these important pulmonary molecules in ventilated neonates without or with sepsis. Methods: Endotracheal aspirates were collected from preterm neonates born at 23–35 weeks and admitted to the neonatal intensive care unit at the John Radcliffe Hospital, Oxford, UK, from October 2000 to March 2002. Samples were collected at one day to 30 days and analysed for SP‐D, total PC and PC molecular species concentrations using enzyme‐linked immunosorbent assay and mass spectrometry. Results: We found that 8/54 (14.8%) neonates developed sepsis. SP‐D (p < 0.0001), mono‐ and di‐unsaturated PC were significantly increased (p = 0.05), and polyunsaturated PC was significantly decreased (p < 0.01) during sepsis compared to controls. SP‐D:PC ratios were significantly increased during sepsis (p < 0.001), and SP‐D concentrations were directly related to gestational age in neonates with sepsis (r 2  = 0.389, p < 0.01). Conclusion: Increased SP‐D levels and changes in PC molecular species during sepsis were consistent with direct or indirect pulmonary inflammatory processes. Very preterm neonates we able to mount an acute inflammatory innate immune response to infectious challenges, despite low levels of surfactant proteins at birth.